Membangun Sistem Manajemen Risiko untuk Menghadapi Tantangan Bisnis pada UMKM “Huisaeng Dimsum” - Natanegara, Aura Syahida Andryanti; Nur Zaman, Luqman; Sheehan, Sheva Dhaifullah (Teewan Journal Solutions, 2025)
The dimsum business in Indonesia is rapidly growing, but it faces various business challenges that can affect its sustainability and growth. Therefore, this research aims to examine the importance of risk management systems in dimsum businesses and to develop a risk management model that can help entrepreneurs identify, analyze, and manage existing risks. This research uses a qualitative approach with a case study on the dimsum business at Huisaeng Dimsum, Bandung city. involving interviews with the business owner, operational manager, as well as direct observation of the production process and operational management. The research findings indicate that the main risks faced include disruptions in the raw material supply chain, fluctuations in raw material prices, intense competition, and changes in regulatory policies. The data analysis technique implemented from this research is the application of risk management based on the ISO 31000 standard, which includes risk identification, risk analysis, risk evaluation, and risk treatment.